Perturbação hidrológica, estabilidade e diversidade de macroinvertebrados em uma zona úmida (lagoas intermitentes) do semi-árido brasileiro - Silva-Filho, Manoel Inácio (Universidade Federal de São Carlos, 2004)
Intermittent shallow lakes are a kind of wetland of great importance in the Brazilian semiarid area, being characterized by hydrological extremes of flood and drought. These shallow lakes are good model for ecological study because they have discrete boundaries, and are subject to disturbance processes such as drying. The goal of this study was to analyse, in according to the conceptual mark of natural disturbances and ecological stability, the diversity and stability of the macroinvertebrates in three Brazilian semi-arid intermittent lakes during two hydrological cycles. In this study, I also compare the diversity of the macroinvertebrate communities to the hydrological disturbance; analyse the degree of resilience and resistance of the community to the drought, as well as, the relationship between diversity and stability in the community studied. Furthermore, I accomplished the inventory of the fauna of macroinvertebrates of 33 intermittent shallow lakes widespread in the Paraibano semi-arid. The results of this study suggest that (i) flooding and drought are the main disturbance agents in these shallow lakes, which are events of great importance to explain the model of macroinvertebrates succession; (ii) in the lakes studied I did not determined the pattern of macroinvertebrate diversities, because a peculiar pattern of diversity seemed to occur in each hydrological cycle; (iii) the species richness was relatively high and the number of individuals small; (iv) the macroinvertebrate populations varied substantially during the hydrological cycle due to variation of the water level and the impacts of the drought; (v) the resistance and resilience of the macroinvertebrate communities to drought demonstrated to be relatively high; and (vi) the variability of the total biomass of macroinvertebrate communities was lower in the lake that exhibited high species richness, while the variability of the abundance of the populations in each species was lower in the lakes with larger species richness of macroinvertebrates.
Keywords: Inter-relações específicas de organismos e meio ambiente; Macroinvertebrados bentônicos; Diversidade de espécies; Lagoas intermitentes; CIENCIAS BIOLOGICAS::ECOLOGIA